Towards a comprehensive legal framework for the protection of ‘Apologies’in the Malaysian healthcare setting - Saleh, Muhammad Ridhwan; Jahn Kassim, Puteri Nemie (The World Association for Medical Law, 2017)
An adverse consequence in medical treatments tends to cause patients and their families to be overwhelmed with anger, frustration, and desire to retaliate. ‘Apologies’ offered at this point of time tend to have remedial effects in reducing the anger and curbing the motivation to bring matters to the court of law. This will eventually reduce confrontational attitudes amongst the parties and the backlog of cases in the court of law. However, doctors are usually advised by their lawyers not to apologise due to the limitations imposed in their professional indemnity insurance whereby by apologising and admitting fault, it is considered as a breach of the terms in the insurance agreement. Further, the apology may be treated as ‘an admission of guilt’ during legal proceedings. In handling medical disputes in Malaysia, the benefits of apologizing are beyond doubt but in encouraging doctors to apologize, a clear legal framework need to be established to protect the apologies made in certain circumstances for unintentional wrongdoings. Lesson can be learnt from the American, Canadian and Australian experiences in drafting and implementing ‘Apology laws’ as well as making amendments to the law of evidence in their quest to resolve medical disputes in a more amicable manner. It is hoped that the establishment of a ‘structured apology law’ in Malaysia will reduce the number of medical negligence claims, defuse the spur of litigation and ultimately, preserve the sanctity of the relationship between the doctor and patient.